Advancing the circular economy through dynamic capabilities and extended customer engagement: Insights from small sustainable fashion enterprises in the UK. (4th February 2022) - Elf, Patrick; Werner, Andrea; Black, Sandy
Abstract: The circular economy holds the potential to significantly reduce resource use. However, attempts to fully utilize its potential have fallen short so far. Based on a longitudinal interview‐based study, we examine how micro, small and medium enterprises (MSMEs) in the UK fashion industry advance the circular economy (CE). Whereas the dynamic capabilities framework is mostly used for medium and large businesses, our findings advance the current literature, demonstrating how the distinctive development and use of dynamic capabilities enable MSMEs to act in agile ways, allowing them to introduce, test and advance CE solutions, while providing them with more resilience during times of crises. Our study further shows that fashion MSMEs adopt circular economy business models (CEBMs) by going beyond conventional, technology‐focused approaches currently dominating business thinking. The research highlights MSMEs' ability to engage in circular practices through an extension of existing business models in the form of close interactions with their customers demonstrating the importance and potential of extended business‐customer engagement in businesses' attempts to adopt CE practices.